(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
Although it was actually started more than ten years ago by survivor Tarana Burke as a means for women, especially Black women, to offer support to others who had endured sexual assault, the rapid spread of MeToo as a hashtag and a movement came in fall 2017 when several Hollywood actresses commented on the frequency of sexual assault and harassment in that industry. Alyssa Milano is often credited with starting the movement but has repeatedly acknowledged Burke. Milano was spurred to use the phrase MeToo when actress Rose McGowan accused Hollywood mogul Harvey Weinstein of rape. It wasn’t just Weinstein, however. The movement did prompt action against the accused in many cases — sometimes legal and other times shaming them within the industry. Yet there are definite limitations to the “callout culture.